Creativity and destruction in Bjarte Breiteig’s «They don’t mourn down there» - Brumo, John (Nordlit, 2024)
How can we interpret Bjarte Breiteig’s short story «Der nede sørger de ikke» (They Don’t Mourn Down There)? The short story depicts two teenage boys who, seemingly without reason, vandalize the arts and crafts rooms at their school. However, on a symbolic level, their destructive actions are connected to themes of suicide, creativity, and individuality.